Different outcomes of never-treated and treated patients with schizophrenia: 14-year follow-up study in rural China. (December 2015) - Ran, Mao-Sheng; Weng, Xue; Chan, Cecilia Lai-Wan; Chen, Eric Yu-Hai; Tang, Cui-Ping; Lin, Fu-Rong; Mao, Wen-Jun; Hu, Shi-Hui; Huang, Yue-Qin; Xiang, Meng-Ze
Abstract : Background: The long-term outcome of never-treated patients with schizophrenia is unclear. Aims: To compare the 14-year outcomes of never-treated and treated patients with schizophrenia and to establish predictors for never being treated. Method: All participants with schizophrenia ( n = 510) in Xinjin, Chengdu, China were identified in an epidemiological investigation of 123 572 people and followed up from 1994 to 2008. Results: The results showed that there were 30.6%, 25.0% and 20.4% of patients who received no antipsychotic medication in 1994, 2004 and 2008 respectively. Compared with treated patients, those who were never treated in 2008 were significantly older, had significantly fewer family members, had higher rates of homelessness, death from other causes, being unmarried, living alone, being without a caregiver and poor family attitudes. Partial and complete remission in treated patients (57.3%) was significantly higher than that in the never-treated group (29.8%). Predictors of being in the never-treated group in 2008 encompassed baseline never-treated status, being without a caregiver and poor mental health status in 1994. Conclusions: Many patients with schizophrenia still do not receive antipsychotic medication in rural areas of China. The 14-year follow-up showed that outcomes for the untreated group were worse. Community-based mental healthcare, health insurance and family intervention are crucial for earlier diagnosis, treatment and rehabilitation in the community.